Investigating the depression, anxiety, and stress-related factors in near-miss mothers - Marjan Amiri; Shahnaz Kohan; Zeinab Heidari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Life-threatening complications during pregnancy and childbirth could have an impact on the physical and mental health of mothers. The present research aimed to investigate the factors related to depression, anxiety, and stress among mothers who have survived maternal near-miss situations. MATERIALS AND METHODS: This is a descriptive-analytical study, and the data have been collected cross-sectionally. Near-miss mothers who had given birth within the past year were selected through the census method (having at least one criterion of the clinical, laboratory, and management standard of the World Health Organization). The Depression, Anxiety, and Stress Scale (DASS-21) and a demographic questionnaire on personal, family, fertility, and care information were filled out by these mothers. RESULTS: One hundred fifty-four near-miss mothers were investigated. The findings indicated that lack of social support, domestic violence, and marital dissatisfaction leads to a significant increase in the mean score of depression among near-miss mothers. In addition, according to the findings, an unemployed spouse, low level of education, lack of social support, recent unintended pregnancy, high blood pressure, and bleeding during pregnancy result in a significant increase in the mean score of stress among near-miss mothers. The findings also showed that domestic violence, a history of infertility, heart disease, and bleeding complications significantly increase anxiety in near-miss mothers. CONCLUSION: Considering the high levels of depression, anxiety, and stress in near-miss mothers, it is of utmost importance to pursue and check up on their mental health, as they are one of the most vulnerable groups in society. It is crucial to provide them support long after discharge to reintegrate these mothers into normal living as per the present study's findings.